Engraved gems and propaganda in the Roman Republic and under Augustus - Gołyźniak, Paweł, (Archaeopress Roman archaeology ;, 2020)
This work studies small but highly captivating artworks from antiquity - engraved gemstones. These objects had multiple applications, and the images upon them captured snapshots of people's beliefs, ideologies, and everyday occupations. They provide a unique perspective on the propaganda of Roman political leaders, especially Octavian/Augustus.